Secondary organic aerosol formation from evaporated biofuels: comparison to gasoline and correction for vapor wall losses. Issue 7 (19th June 2020) - He, Yicong; King, Brandon; Pothier, Matson; Lewane, Liam; Akherati, Ali; Mattila, James; Farmer, Delphine K.; McCormick, Robert L.; Thornton, Matthew; Pierce, Jeffrey R.; Volckens, John; Jathar, Shantanu H.
Abstract : With an ongoing interest in displacing petroleum-based sources of energy with biofuels, we measure and model the formation and composition of secondary organic aerosol (SOA) from organic compounds present in biofuels. Abstract : With an ongoing interest in displacing petroleum-based sources of energy with biofuels, there is a need to measure and model the formation and composition of secondary organic aerosol (SOA) from organic compounds present in biofuels. We performed chamber experiments to study SOA formation from four recently identified biofuel molecules and mixtures and commercial gasoline under high NO x conditions: diisobutylene, cyclopentanone, an alkylfuran mixture, and an ethanol-to-hydrocarbon (ETH) mixture. Cyclopentanone and diisobutylene had a significantly lower potential to form SOA compared to commercial gasoline, with SOA mass yields lower than or equal to 0.2%. The alkylfuran mixture had an SOA mass yield (1.6%) roughly equal to that of gasoline (2.0%) but ETH had an average SOA mass yield (11.5%) that was six times higher than that of gasoline. We used a state-of-the-science model to parameterize or simulate the SOA formation in the chamber experiments while accounting for the influence of vapor wall losses. Simulations performed with vapor wall losses turned off and at atmospherically relevant conditions showed that the SOA mass yields were higher than those measured in the chamber at the same photochemical exposure and were also higher than those estimated using a volatility basis set that was fit to the chamber data. The modeled SOA mass yields were higher primarily because they were corrected for vapor wall losses to the Teflon® chamber.